A new method to couple FEM mooring program with CFD to simulate Six-DoF responses of a moored body. (15th April 2022) - Huang, Han; Gu, Haoyuan; Chen, Hamn-Ching
Abstract: The objective of this study is to develop an accurate and efficient coupled program, which incorporates computational fluid dynamics, a six-DoF motion solver, and nonlinear finite-element cable analysis program MOORING3D. The new coupled method aims at studying dynamic responses of moored structures in environments which cannot be modeled by conventional approach. The novelty of the coupled method also lies in that we develop the methodology for an overset grid system of embedding, overlapping, and moving structured grids. Large eddy simulation was used as the turbulence model. The level-set method was applied to capture free surface effects. Two buoys were studied. Wave-induced motions of the first buoy were simulated by both coupled CFD-mooring method and commercial software. The discrepancy was investigated to illustrate advantages of the coupled method in addressing viscous and nonlinear hydrodynamic effects. The wave-current-body interaction of another buoy was simulated with RAOs being compared against experiments and vortex-induced motion being investigated. The conclusions indicated that the coupled CFD-FEM method provides feasible solutions for floating systems exposed to complicated environmental conditions. Highlights: A new method is proposed to couple CFD model with FEM mooring analysis program. Level-set method is used to model free surfaces and nonlinear hydrodynamic effects. The new method is superior to conventional one in capturing viscous and eddy effect. The wave-induced motions of buoys are verified against experiments. VIM can be modeled by the coupled method and shows reduction with waves.